The psychometric properties of PSYCHLOPS, an individualized patient‐reported outcome measure of personal distress - Sales, Celia (2022)
Objective Few studies report the psychometric properties of individualized patient-reported outcome measures (I-PROMs) combining traditional analysis and Item Response Theory (IRT). Methods Pre- and posttreatment PSYCHLOPS data derived from six clinical samples (n = 939) were analyzed for validity, reliability, and responsiveness; caseness cutoffs and reliable change index were calculated. Exploratory and confirmatory factor analyses were used to determine whether items represented a unidimensional construct; IRT examined item properties of this construct. Results Values for internal consistency, construct validity, convergent and discriminant validity, and structural validity were satisfactory. Responsiveness was high: Cohen's d, 1.48. Caseness cutoff and reliable clinical change scores were 6.41 and 4.63, respectively. IRT analysis confirmed that item scores possess strong properties in assessing the underlying trait measured by PSYCHLOPS. Conclusion PSYCHLOPS met the criteria for norm-referenced measurement of patient psychological distress. PSYCHLOPS functioned as a measure of a single latent trait, which we describe as "personal distress."